Des conditions carcérales dans la Prison Centrale de Kisangani en République Démocratique du Congo. - Muzaliwa, Andy DJUMA (IJRDO - Journal of Social Science and Humanities Research, 2021)
While in prison, detainees retain their fundamental rights, hence the obligation to treat them with dignity and humanity. Legislation at the international and national level exists in favor of residents of prisons in the Democratic Republic of Congo in general and the central prison of Kisangani in particular, these standards govern the material conditions in which people placed in detention must be imprisoned. These standards lead to respect for minimum rules in terms of separation of categories of detainees, detention facilities, hygiene, food, medical care, information to detainees on their rights, discipline and punishments, contact and communication with the outside world, work, physical exercise, religion, etc. It is clear that these standards only exist on a theoretical level, whereas in practice the situation is totally disappointing. So a considerable gap is observed between the existing rules and their application in the field.